2018
DOI: 10.1016/j.mambio.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Lack of mate selectivity for genetic compatibility within the red brocket deer Mazama americana complex

Abstract: Red brocket deer Mazama americana includes at least two lineages that differ at the level of karyotypes and phylogenetic relationships based on mtDNA. Also, hybrids between them have been proved to be nonviable or infertile. Since successful breeding is hampered, we expect selection to have produced a precopulatory barrier between these lineages based on courtship behaviour, to prevent investment in unsuccessful breeding. Here we made experiments with specimens in captivity to investigate mating preferences fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…There are no reports of hybrids in the wild, although a weak pre-mating isolation barrier between species has been observed in captivity [ 63 ]. Regarding MAM, reports of captive crossbreeding between cytotypes already exist [ 25 , 75 ], which are explained by the verified lack of a clear pre-mating barrier [ 26 ]. However, it is difficult to say that this can happen in nature, despite the geographical proximity between MGO and MNE, as well as between the MAM cytotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no reports of hybrids in the wild, although a weak pre-mating isolation barrier between species has been observed in captivity [ 63 ]. Regarding MAM, reports of captive crossbreeding between cytotypes already exist [ 25 , 75 ], which are explained by the verified lack of a clear pre-mating barrier [ 26 ]. However, it is difficult to say that this can happen in nature, despite the geographical proximity between MGO and MNE, as well as between the MAM cytotypes.…”
Section: Discussionmentioning
confidence: 99%
“…A reproductive study on MAM showed that hybrids produced by crossbreeding of the two different chromosomal linages are sterile [ 25 ]. This indicated the occurrence of post-zygotic reproductive isolation between the MAM linages, which was associated with errors in meiotic recombination and gametic segregation due to several chromosomal differences, such as TF, RT, and inversions [ 25 , 26 ]. Hybrids between cytotypes of the same chromosomal lineage, with a chromosome number difference being equal to or less than 3 between the parents, were considered subfertile.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the difference of one tandem fusion between M. rufa and the Carajás cytotype (MRU 5/8, forming CA3) has been described ( Abril et al, 2010 ; Galindo et al, 2021 ). The potential hybridization between both populations would lead to the formation of individuals carrying one tandem fusion in heterozygosis, considering the conservative observation of absence of a prezygotic barrier in captivity ( Carranza et al, 2018 ). Such rearrangement is considered deleterious and with a hypothetical 50% reduction in the production of balanced gamete ( King, 1993 ), resulting in reduced fertility of the carrier ( Moritz, 1986 ; Pillay et al, 1995 ; Long, 1996 ; Galindo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in a conservative taxonomic approach, the greatest chromosomal divergence among populations (>3 chromosome pairs) represented a post-zygotic reproductive barrier. This indicates the presence of two species in the M. americana complex correspondent to the two described lineages (Abril et al, 2010;Cursino et al, 2014;Salviano et al, 2017;Carranza et al, 2018). In a less conservative taxonomic approach, the subfertility observed among populations with a minor divergence (1 or 2 chromosome pairs) would already represent isolation, leading to the hypothesis that each cytotype could correspond to a distinct species (Abril et al, 2010;Cursino et al, 2014;Salviano et al, 2017;Carranza et al, 2018;Galindo et al, 2021).…”
Section: Introductionmentioning
confidence: 96%
“…It is important to consider that accumulation of chromosomal rearrangements causes meiotic segregation errors with chromosome pairing limitations (Villagómez and Pinton 2008; Dobigny et al 2017). Specifically, the difference of more than two pairs of chromosomes has been described as a reproductive barrier in M. americana cytotypes, with tandem fusion as the mean causes of reduction in hybrid fertility considering the chance of successful reproduction in a backcross breeding with animals from the parent populations (Cursino et al 2014;Salviano et al 2017;Carranza et al 2018). A recent study evaluated the meiotic segregation of hybrids with one heterozygotic tandem fusion in the M. americana com-plex, including a hybrid between the Carajás and Paraná cytotypes obtaining a rate of ~30 % gametic unbalance (Galindo et al 2021b).…”
Section: Discussionmentioning
confidence: 99%